Crustal deformation characteristics of Sichuan-Yunnan region in China on the constraint of multi-periods of GPS velocity fields. Issue 8 (15th April 2018) - Yue, Caiya; Dang, Yamin; Dai, Huayang; Yang, Qiang; Wang, Xiankai
Abstract: In order to obtain deformation parameters in each block of Sichuan-Yunnan Region (SYG) in China by stages and establish a dynamic model about the variation of the strain rate fields and the surface expansion in this area, we taken the Global Positioning System (GPS) sites velocity in the region as constrained condition and taken advantage of the block strain calculation model based on spherical surface. We also analyzed the deformation of the active blocks in the whole SYG before and after the Wenchuan earthquake, and analyzed the deformation of active blocks near the epicenter of the Wenchuan earthquake in detail. The results show that, (1) Under the effects of the carving from India plate and the crimping from the potential energy of Tibetan Plateau for a long time, there is a certain periodicity in crustal deformation in SYG. And the period change and the earthquake occurrence have a good agreement. (2) The differences in GPS velocity fields relative Eurasian reference frame shows that the Wenchuan earthquake and the Ya'an earthquake mainly affect the crustal movement in the central and southern part of SYG, and the average velocity difference is about 4–8 mm/a for the Wenchuan earthquake and 2–4 mm/a for the Ya'an earthquake. (3) For the Wenchuan earthquake, the average strain changed from 10 to 20 nanostrian/a before earthquake to 40–50 nanostrian/a after the earthquake, but before and after the Ya'an earthquake, the strain value increased from about 15 nanostrian/a to about 30 nanostrian/a. (4) The Wenchuan earthquake has changed the strain parameter of each active block more or less. Especially, the Longmen block and Chengdu block near the epicenter. The research provides fundamental material for the study of the dynamic mechanism of the push extrusion from the north-east of the India plate and the crimp from Qinghai Tibet Plateau, and it also provides support for the study of crustal stress variation and earthquake prediction in Sichuan Yunnan region.